Adenomatoid odontogenic tumor of the mandible with a large calcified mass: Report of a rare case. Issue 1 (January 2015) - Higo, Morihiro; Sato, Toyohiko; Komatsu, Teisuke; Takahashi, Kikuo
Abstract Adenomatoid odontogenic tumors (AOTs), relatively uncommon benign lesions of odontogenic epithelial origin, are categorized into three clinicopathological variants: follicular, extrafollicular, and peripheral. We present a rare case of follicular AOT with an impacted tooth and a large calcified mass. A 13-year-old girl was referred by her orthodontist for evaluation of the delayed eruption of a left mandibular lateral incisor and a radiopaque mass of the anterior mandible. Computed tomography showed an odontoma-like radiopaque mass adjacent to the crown of the impacted left mandibular lateral incisor inside the radiolucent area. The lesion was enucleated totally as one mass with the unerupted tooth under general anesthesia. The histopathologic findings, such as the cuboidal or columnar epithelial cells forming duct-like or rosette-like structures and intercellular droplets of amorphous eosinophilic material, corroborated the AOT characteristics reported in the literature. However, the large calcified mass was a rare finding in follicular AOT. The current case of AOT was difficult to distinguish from the more common forms of odontogenic lesions. There have been no signs of recurrence of the AOT 14 months postoperatively.